Pengaruh Pemberian Pendidikan Kesehatan Tentang Pencegahan Pasung Terhadap Pengetahuan Dan Sikap Kader Kesehatan Di Desa Mancasan - Claudia, Ranggraita Ayu; , Arif Widodo, A Kep., M.Kes (2016)
ABSTRACT Ranggraita Ayu Claudia1, J 210120010, Arif Widodo, A.Kep., M.Kes2 GIVING EFFECT OF HEALTH EDUCATION PREVENTION OF KNOWLEDGE AND ATTITUDE TOWARDS STOCKS CADRE HEALTH IN THE VILLAGE MANCASAN Sukoharjo region in 2011-2013 there were approximately 2778 cases of mental disorders in the various districts of the region Sukoharjo.Sedangkan patients who have stocks ranging from 2011-2013 as many as 43 pasien.Salah the region with the most mental patients are village Mancasan, This study aimed to determine differences in knowledge and attitudes regarding prevention of mental health cadres stocks before and after health education in the Village Mancasan District of Sukoharjo Baki. This research is a quantitative research and type of research is a quasi-experimental study. The population in this study were all health cadres Mancasan In the village of Sukoharjo District of Baki which amounted to 51 cadres. The sample used in this study is total sampling which amounted to 51 cadres. These results indicate that there are differences signikan anatara knowledge before being treated after being given the education of health and health education are indicated by Asymp. Sig. 0.000 <0.05 as well as the attitude of the respondents there are differences in attitudes before and after the treatment given health education. Keywords: Knowledge. Attitude. Health Education